PERAN AUDIT INTERNAL, SISTEM PENGENDALIAN INTERNAL DAN KOMITMEN MANAJEMEN DALAM PENERAPAN GOOD CORPORATE GOVERNANCE - Ruwaidha, Hayatun; Kundati, Cris (Publika Citra Media, 2024)
The aim of this research is to determine the extent of the role of internal audit, internal control systems and management commitment in implementing Good Corporate Governance in corporate governance. This research uses a literature study which refers to certain research and development carried out to collect and evaluate research related to a particular topic focus. This literature shows that 1) Internal Audit has an influence on GCG; 2) The Internal Control System influences GCG and 3) Management Commitment influences GCG.